Roles of Platelets and Factor XI in the Initiation of Blood Coagulation by Thrombin - Walsh, Peter N. (Thrombosis and Haemostasis, 2001)
To account for the variable hemostatic defect in patients with factor XI (FXI) deficiency, with normal hemostasis in contact factor deficiencies, a coagulation paradigm is presented whereby trace quantities of thrombin, generated transiently by exposure of tissue factor at sites of vascular injury, activates FXI bound to the platelet surface in the presence of prothrombin or high Mr kininogen (HK). Tissue factor pathway inhibitor (TFPI) limits the flux of thrombin generated by the tissue factor pathway, and protease nexin II (PNII), released from activated platelets, inhibits solution phase FXIa and localizes FIX activation to the platelet surface where FXIa is protected from inactivation by PNII. Either prothrombin or HK binds to the Apple 1 (A1) domain of FXI, thereby exposing a platelet-binding site in the FXI A3 domain. Dimeric FXI binds to activated platelets directly through the A3 domain of one monomer. After proteolytic activation of platelet-bound FXI by thrombin (or FXIIa), a substrate binding site for FIX is exposed in the opposite monomer that promotes FIX activation on the platelet surface resulting in the local explosive generation of thrombin and the formation of hemostatic thrombi at sites of vascular injury.
Keywords: Factor XI; factor IX; protease nexin II; factor XII; high Mr kininogen